บริการ OTT: ความท้าทายต่อสื่อเก่าและการกำกับดูแล - จรินทิพย์พิทักษ์ นางรมิดา (Journal of Digital Communications, 2017)
The article explores the documentary research method and aims to provide a general understanding of the new service, called OTT or Over-the-Top which affects the persistence of traditional media. The issue of unbalanced regulation between OTT as new media and traditional media was discussed in many countries. This article proposed the policy recommendations for regulating OTT services. Due to the availability of high speed wireless broadband and easier access to a wider range of devices, OTT services have experienced unprecedented growth. So a key challenge in this new era is how to regulate the growing number of onshore and offshore OTT services. Thailand is necessary to support growth in the OTT market because it is considered as a new choice for audiences and technology advances beyond the limited scope of these new media services but consideration for appropriate regulation has the necessary threat as well. Policymakers across the globe are looking at the regulation of OTT services in some of sensitive areas. Regulatory framework must therefore rely on the collaboration of several agencies and stakeholders. In some cases, those may not operate under the jurisdiction of the laws of one country; it should operate by cross countries ‘compliance. For the Net neutrality policy, Thailand should consider very carefully the effect results. In addition, the measures to support and motivation in producing the local content by assigning a proportion is an issue of priority as well.